Workarounds and Test Results Follow-up in Electronic Health Record-Based Primary Care - Menon, Shailaja; Murphy, Daniel R.; Singh, Hardeep; Meyer, Ashley N. D.; Sittig, Dean F. (Applied Clinical Informatics, 2016)
Electronic health records (EHRs) have potential to facilitate reliable communication and follow-up of test results. However, limitations in EHR functionality remain, leading practitioners to use workarounds while managing test results. Workarounds can lead to patient safety concerns and signify indications as to how to build better EHR systems that meet provider needs.To understand why primary care practitioners (PCPs) use workarounds to manage test results by analyzing data from a previously conducted national cross-sectional survey on test result management.We conducted a secondary data analysis of quantitative and qualitative data from a national survey of PCPs practicing in the Department of Veterans Affairs (VA) and explored the use of workarounds in test results management. We used multivariate logistic regression analysis to examine the association between key sociotechnical factors that could affect test results follow-up (e.g., both technology-related and those unrelated to technology, such as organizational support for patient notification) and workaround use. We conducted a qualitative content analysis of free text survey data to examine reasons for use of workarounds.Of 2554 survey respondents, 1104 (43%) reported using workarounds related to test results management. Of these 1028 (93%) described the type of workaround they were using; 719 (70%) reported paper-based methods, while 230 (22%) used a combination of paper- and computer-based workarounds. Primary care practitioners who self-reported limited administrative support to help them notify patients of test results or described an instance where they personally (or a colleague) missed results, were more likely to use workarounds (p=0.02 and p=0.001, respectively). Qualitative analysis identified three main reasons for workaround use: 1) as a memory aid, 2) for improved efficiency and 3) for facilitating internal and external care coordination.Workarounds to manage EHR-based test results are common, and their use results from unmet provider information management needs. Future EHRs and the respective work systems around them need to evolve to meet these needs.
Keywords: Workarounds; diagnostic test result follow-up; paper-based methods; missed test results